Biocementation beyond the Petri dish, scaling up to 900 L batches and a meter-scale column - Dimitrios Terzis; Camilla Perego; Margherita Cappa; Elisa Pianta; Federica Mauri; Pamela Principi (Scientific Reports)
Abstract Microbial-induced calcite precipitation (MICP), which leverages ureolytic microorganisms, has received significant attention during the past decade as a promising method for sustainable building and geoenvironmental applications. However, transitioning from lab-scale experimentation to volumes suitable for practical use poses challenges. This study addresses these obstacles by screening and analyzing over 50 strains sourced from (i) a natural environment in the canton of Ticino in Switzerland; (ii) microorganism banks; and (iii) an industry-scale bioreactor. Several ureolytic Sporosarcina species have been identified in the natural environment, and their ureolytic potential has been compared with that of other strains. A reference, banked microorganism yielded the highest ureolysis rate. When this latter strain was inoculated in 900 L batches and continuously cultivated at 5400 L, no contamination issues were observed, and the reference strain remained the dominant species. The produced culture, obtained under an optimized medium composition involving the circular valorization of NH4 +, was subsequently used to induce the biocementation of a 650 kg column of 0–1 mm sand. The results reveal the successful stabilization of the whole mass, with undrained Tresca strength values ranging from 90 to 140 kPa. This research lays the groundwork for scalable MICP production, which is capable of meeting the demands of real-world building and geoenvironmental projects.